JIGSAW COOPERATIVE LEARNING MODEL USING AUDIOVISUAL MEDIA TO IMPROVE LEARNING OUTCOMES - Wahyu Bagja Sulfemi; Yasinta Kamalia (JPSD (Jurnal Pendidikan Sekolah Dasar), 2020)
This research is a classroom action research that aims to improve student learning outcomes in Social Sciences learning by using a jigsaw cooperative learning model with the help of audiovisual media. The study was conducted at the Al-Hamidiyah Integrated Islamic Elementary School Class III Khalid Bin Walid, amounting to 25 people consisting of 14 men and 11 women. The research was carried out starting from the lack of student learning outcomes in learning, from the results of the worksheets given to students there are about 56% of students who are still below the Maximum Mastery Criteria that is set that is 75. Together with colleagues to improve learning by two cycles. Each cycle consists of planning, implementation, observation, and reflection. Data collected in this study are quantitative data in the form of learning outcomes. The results of this study's data analysis showed an increase in the percentage of student learning outcomes also increased, from 60% in cycle 1 to 80% in cycle 2. The results of this study can be concluded that the use of the Jigsaw Cooperative Learning Model assisted with audiovisual media can improve learning outcomes. Keywords: jigsaw; audiovisual; and learning outcomes